Jan Van Eyck and the Ghent Altarpiece. Issue 3 (3rd July 2018) - Pettersson, Rune
Abstract: The painter Jan Van Eyck is one of the most significant representatives of Northern Renaissance art. The brothers Van Eyck painted the large almost 600-year-old Ghent Altarpiece. This polyptych with 26 paintings is an impressive rendering of Catholic mysticism. Jan Van Eyck used new techniques of handling both oil paint and transparent glazes. He was an early light designer and painted realistic lighting and shadows. Jan Van Eyck used central perspective, eye-level perspective and worm's-eye perspective in his paintings. He was the first to use aerial perspective. Jan Van Eyck included numerous verbal messages and symbols in his paintings, designed in every detail.